Preposisi dalam Bahasa Kaili - Tamrin Tamrin (Kantor Bahasa Provinsi Maluku Utara, 2014)
Kaili language is the language spoken in Central Sulawesi. as the native language, Kaili language plays an important role in the society. Therefore, as a local language, Kaili language needs to bemaintained and preserved. This research aimed at (1) describing and determining the forms of prepositionin Kaili language and (2) describing the function of prepositions in the sentence. Interview was doneas the method of the research. The results show that there are two forms of prepositions in Kaili Language. They are single preposition and combined preposition. Single preposition consists of rootword and prefix preposition while combined preposition consists of adjoining preposition, correlated preposition, and locative nominal preposition. Prepositions in Kaili language may function as placemarker, causative marker, manner marker, time marker, purposive marker, and comparative marker.